Land reclamation using soft clay fill and vacuum preloading via horizontal drainage enhanced geotextile sheets - Chen, Hao (Nanyang Technological University, 2022)
In land-scarce Singapore, land reclamation or other space creation methods are required to cater for future economic development. With the shortage of granular fill materials, other alterative fill materials such as soft marine clay have to be utilized for land reclamation. For the improvement of soft clay, the conventional methods adopted are preloading using either fill surcharge or vacuum pressure with prefabricated vertical drains (PVDs). However, for very soft clay, the preloading using PVDs method is time consuming and technically challenging. The difficulties include the need to form a working platform, the inability to carry out soil improvement during the fill material placement and the construction of containment structures in relatively deep water. The objective of this study was to develop improved methods for land reclamation using soft soil. The Broms’ method of using geotextile sheets and sand berms was modified to facilitate the formation of a working platform on top of very soft clay. An analytical method was developed for the Modified Broms’ method to predict the profile of the deformed geotextile and the distribution of tensile strain at the critical condition. Design charts for considering the contact width and the spacing of sand tubes and the property of geotextile were proposed to facilitate the design. To overcome the difficulties involved in the land reclamation methods using PVDs, a soil improvement method using horizontal drainage enhanced geotextile sheet (HDeG sheet) and vacuum preloading was developed for land reclamation using soft clay fill. Model tests were carried out to study the consolidation behaviour of soft soil around HDeG and the effectiveness of the HDeG method. The results of the model tests indicated that the HDeG method was effective and the effectiveness of the HDeG was much affected by the transmissivity of the geotextile. For the same drain size and spacing, better performance in terms of settlement and pore water pressure dissipation was achieved when non-woven geotextile with better transmissivity was used. A method to measure the transmissivity of non-woven geotextile in clay was also proposed. The testing data indicate that the transmissivity of non-woven geotextile was affected by the type of soil and the applied normal stress. Both 2D small strain and large strain solutions were proposed for analysing vacuum consolidation of soft clay with the use of HDeG. A horizontal drain element was developed to model the drainage property of HDeG including the transmittivity of geotextile using the ABAQUS/Standard software. In terms of settlements and excess pore pressure distributions, the results using the proposed consolidation solutions were consistent with those measured in the model tests and those simulated using finite element analysis (FEA). The degree of consolidation computed using the proposed consolidation solutions using either settlements or pore pressure distributions was also consistent with that calculated using the data from the model tests and those from FEA. Theoretically, the degree of consolidation based on pore pressure distribution may lag behind that based on soil surface settlement. The difference was caused by the non-linear compressibility of soft clay. An equation for converting the degree of consolidation based on settlement to that based on pore pressure or verse versa was also proposed. To improve the performance of HDeG, two new methods were proposed. The first was the use of electro-osmosis with HDeG or electrical HDeG, and second was the use of lime liner with HDeG or lime liner enhanced HDeG. The former incorporated electro-osmosis with HDeG to enhance or accelerate the rate of consolidation using HDeG. The later used a thin layer of lime to improve the permeability along the soil-HDeG interface. Laboratory model tests were carried out. The testing data indicated that the electrical HDeG could improve the consolidation of soft soil particularly for soil that has been consolidated under vacuum pressure, and by using the lime liner enhanced HDeG, the permeability of soil near the HDeG could be improved by 2 to 3 times. Due to sea level rise and previous land reclamation activities, future land reclamation would have to be carried out in relatively deep water. A method for constructing vertical containment structure for land reclamation using prefabricated concrete cylinders and suction caissons was proposed. Design methods for stability and deformation analyses were proposed. The results from the proposed method agreed well with those from the finite element analysis.